68.6k views
5 votes
If G(X) = 3x+1, then G-1(1) is

If G(X) = 3x+1, then G-1(1) is-example-1
User Nosklo
by
5.0k points

1 Answer

1 vote

Answer:

0

Explanation:

To find the inverse, or
G^(-1) , we must switch G(x) and x, and then make G(x)
G^(-1) (x) as we are finding the inverse, and G(x) represents the starting equation.


x = 3G^(-1) (x)+1\\x -1 = 3G^(-1) (x)\\\\(x-1)/(3) = G^(-1) (x)\\

The steps used here are that we firt subtracted 1 from both sides, and then divided 3 from both sides.

To find
G^(-1) (1), we simply plug 1 into x in the inverse function, so our answer is
(1-1)/(3) =0

User Douglas Meyer
by
4.3k points